PENTINGNYA ALOKASI BIAYA LINGKUNGAN TERHADAP KINERJA LINGKUNGAN DAN PROFITABILITAS PERUSAHAAN - Hapsari, Hannisa Rahmadani; Irianto, Bambang Setyobudi; Rokhayati, Hijroh (Jurnal Riset Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of environmental costs on profitability mediated by environmental performance. The population in this study are public companies in Indonesia that participated in PROPER during the 2013-2018 period. The sampling technique uses purposive sampling. The unit of analysis in this study is the company year so that 64 research data are obtained. Data analysis techniques used in this study are simple regression analysis and mediation tests using the Sobel test and path analysis. The results of this study indicate that: (1) Environmental costs have a positive effect on profitability; (2) Environmental costs have a positive effect on environmental performance; (3) Environmental performance has a positive effect on profitability; (4) Environmental performance cannot mediate the relationship between environmental costs and profitability.